The seemingly anomalous price behavior of Royal Dutch/Shell and Unilever N.V./PLC - Rosenthal, L (Journal of Financial Economics, 1990)
We examine two Anglo-Dutch groups the shares of whose parents trade on several international exchanges. Within each group, the parents' corporate charters mandate the division of cash flows available for distribution. This implies a specific ratio for the market prices of their securities. We document persistent deviations from these ratios on both the New York and London exchanges. The direction and magnitude of the mispricing are common to both pairs of stocks and both markets. Nevertheless, we find no evidence of profitable intra- or intermarket trading rules.